Animal Models and Experimental Research in Medicine - Karapehlivan, Mahmut; Gelen, Volkan; Kükürt, Abdulsamed (IntechOpen, 2023)
The use of experimental animals is quite common in medical research, especially for pharmaceutical developments and molecular pathway studies. Considering the effects of therapeutic agents used in the treatment of tissues and systems, it becomes clear how important experimental animals and the models developed on them are in research. The benefits of using animals for disease models include accessibility, applicability, and affordability. Most importantly, they have proven to be successful in the prevention, diagnosis, and treatment of many diseases. This book provides a comprehensive overview of the use of animal models for amyotrophic lateral sclerosis, hepatotoxicity, liver fibrosis/cirrhosis, visceral hyperalgesia, female reproduction, and more.